GERAKAN SOSIAL POLA HIDUP BERSIH DAN SEHAT (PHBS) PADA MASYARAKAT SITAPUANG KANAGARIAN BALAI GURAH KECAMATAN AMPEK ANGKEK - Thami Syaroya; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The title of this research is “The Social Movement the Clear And Healthy (PHBS) In Society Sitapuang Kanagarian Balai Gurah the District Ampek Angkek”. This research aims to know the implementation of clean living and healthy (PHBS) set by the Department of Health (DEPKES) the Sitapuang Kanagarian Balai Gurah and to Know the faktor in the social movement a clean lifestyle and healthy at the Sitapuang. The This research uses qualitative analysis method, the subject of this research is determined by purposive sampling techniques and data collection techniques using observation, interviews, and documentation. The results of this study shows that many people who throw trash on the river Sitapuang, which resulted in the buildup of waste in the river. As for the implementation of the 10 Indicators of the conduct of life clean and healthy (PHBS) the Sitapuang Kanagarian Balai Gurah, delivery be helped by the health, breastfeeding exlusive, to weigh the babies and toddlers, using clean water, wash your hands with clean water and soap, using the toilet, finishing larvae at home, eating fruits and dawn every day, do do intentional physical activity every day, and don’t smoke in the house. And these factors social movement a clean lifestyle and healthy at the Sitapuang, Improving in the Sitapuang. order stakeholders in the environmental community, the efforts of the community in creating the village clean.The key word : The Social, Lifestyle, Clean and Healthy